Evaluasi Saluran Drainase pada Jalan Purwodadi Kecamatan Lawang Kabupaten Malang - Soares, Pedro Afonso; Suhudi, Suhudi; Irvani, Harvi (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2018)
ABSTRACT The System of drainage channels is necessary to throw away the rain water is not absorbed in the soil, as well as to prevent the occurrence of puddles that can interfere with the activities of the community or cause flooding during the rainy season. The problem of puddles into thought and attention from various parties, it is because of the lack of enthusiasm of the community and lack of drainage channels inside or around the area of Purwodadi Subdistrict Lawang. This research was carried out in Purwodadi Subdistrict Lawang Regency Malang, from the month of October â November 2016. The methods used in this study are of rational methods i.e. Qa = 0.278. C. I. A, While the data obtained from the research is the condition of the road and the Existing channel that suffered damage and also data from multiple instances include: precipitation Data, Map land use. From the results of the data analysis States that the amount of rainfall with the 10-year anniversary of the epoch of 61.238 mm, Kala flood discharge 10-year anniversary of sal: Q. = 1.0 m3/sec. the capacity of the existing drainage channels of Q sal. = 0.889 m3/sec. The dimensions of the existing channels are not enough to miss the kala flood discharge 10-year anniversary of 1.0 m3/sec. Plan of drainage channels: Q sal. = 1.39 m3/sec. Construction design for drainage channels in the path of Purwodadi is b = 0.80 m and h = 1.0 m to keep the puddle does not occur then the dihimbau to the people not to throw garbage on the channel and maintenance on a regular basis by the Office of related and also the community. Key words ; hydrology, hydraulics Analysis, evaluation of Drainage channels.